Pengaruh Pengetahuan dan Sikap Terhadap Perilaku Memilih Bank Syariah Dengan Faktor Religiusitas Sebagai Moderating Variable - Asri Handayani; Heru Aulia Azman; Ismail Ismail (EKONOMIKA SYARIAH : Journal of Economic Studies, 2019)
This study shows the relationship between knowledge and attitude towards the behavior of choosing Islamic banks with moderated religiosity. The study was conducted on 117 people who became customers of Islamic banks in four sub-districts located in the Agam Regency region which has a sharia bank office network, namely Lubuk Basung District, Baso District, Ampek Angkek Canduang District and Banuhampu District. The results of this study indicate that (1) knowledge has a positive and significant effect on the behavior of choosing Islamic banks with a value of P = 0.01, (2) the attitude has a positive and significant effect on the behavior of choosing Islamic banks with a value of P <0.01, (3) religiosity does not moderate relations between knowledge and behavior of choosing Islamic banks with a value of P = 0.46 this indicates that religiosity is not a moderator of the relationship between attitudes and behavior of choosing Islamic banks. (4) While the effect of moderating religiosity on the relationship between attitude and behavior of choosing Islamic banks is significant with a value of P = 0.03 and this shows that religiosity is able to moderate the relationship between attitudes and behavior of choosing Islamic banks.